NAVIGATING SELF-TRANSLATION NUANCES: EFL STUDENTS’ STRATEGIES AND CHALLENGES IN TRANSLATING ENGLISH TEXT - Ekayati, Rini (FKIP Universitas Al Washliyah Medan, 2025)
The skill of translation is considered as one of the abilities that language learners, particularly foreign language learners, should have. In fact, this is particularly true for students of foreign language learners, in this case English, as a Foreign Language (EFL), often navigate the complexities of linguistic proficiency while striving to retain the essence and nuances of the original text. Thus, this study aims to investigates the strategies employed by EFL students to preserve the nu-ances of original texts during self-translation from Bahasa Indonesia to English under five strategies: 1) Intentional Language Selection (ILS), 2) Cultural and Linguistic Sensitivity (CLS), 3) Equivalence and Fidelity (EF), 4) Emotional and Stylistic Impact (ESI), and 5) Hybrid Identities and Third Space (HITS), and challenges faced by EFL students in employing self-translation strategies. Conducting a qualitative research design, 23 EFL students were selected as the source of data, and document of their translated text (academic and non-academic text) were the instrument for collecting the data. Content analysis was used to identify the data to answer the research study. The finding indicated that five proposed self-translation strategies were employed by the EFL students in translation, and challenges they faced were caused by limited linguistic proficiency, cultural awareness, and the cognitive demands of translating complex sentences while preserving the original meaning can also lead to cognitive overload.